(untitled) - Muse, Vance (New York, US, 1998)
The second revised edition in the SMITHSONIAN GUIDES series. A presentation of American historic sites and museums in Northern New England. Features up to date site information which includes location, visiting hours, phone numbers and fee information. Maps and illustrations are included.
Keywords: Historic sites,Khu vực lịch sử; New England,New England